Relationship between multidimensional sleep health and depression during late pregnancy: a cross-sectional study - Yueying Wang; Jinle Wang; Pei Chen; Jiahui Zhang; Qin Lin; Bilgay Izci-Balserk; Yan Li; Bei Bei; Bingqian Zhu (BMC Psychiatry)
Abstract Background Depression is common among pregnant women and identifying modifiable risk factors is critical (e.g., sleep). Individual sleep dimensions, e.g., short sleep duration and poor sleep quality, were associated with a higher risk of depression, while whether the multidimensional construct of sleep health could be a protective or risk factor for prenatal depression remains unknown. This study aimed to examine the relationship between multidimensional sleep health and depression during late pregnancy. Methods This study was conducted among women during late pregnancy (28–40 weeks). Sleep health was measured by self-report questionnaires. Each dimension (sleep quality, duration, efficiency, timing, regularity and daytime sleepiness) was categorized as “good” or “poor”. A composite sleep health score was calculated. Depression was measured using the Edinburgh Postnatal Depression Scale. Logistic regression analyses were used to examine the associations between individual sleep health dimensions and depression. Restricted cubic spline analysis was used to explore the dose-response relationship between overall sleep health and depression. Results A total of 329 women were included. Their mean age was 31.6 years and the mean gestational age was 34.7 weeks. Sixty (18.2%) had clinically elevated depression. There was a dose-response relationship between composite sleep health score and depression, with a higher sleep health score associated with a lower risk of depression (OR = 0.572, 95%CI = 0.423–0.774, p for linearity < 0.001). Controlling for covariates, poor sleep quality (OR = 3.485, 95%CI = 1.817–6.683, p < 0.001), short sleep duration (OR = 3.462, 95%CI = 1.513–7.924, p = 0.003), and excessive daytime sleepiness (OR = 3.409, 95%CI = 1.804–6.442, p < 0.001) were associated with a higher risk of depression. Conclusion Both overall sleep health and individual dimensions (sleep quality, short sleep duration, and daytime sleepiness) were associated with depression during late pregnancy. These findings highlight the potential benefits of maintaining sleep health to achieve mental wellbeing in pregnant women. Healthcare providers may consider adding the assessment and management of sleep health as part of routine prenatal care. Clinical trial number Not applicable.